Pengembangan Buku Penuntun Praktikum Pencemaran Lingkungan dengan Model Argument-Driven Inquiry (ADI) - Zevi Octasari; Neni Hasnunidah; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the validity and practicality of the guiding book of environmental pollution practicum with ADI model. Research development (R and D) using 4-D model are: define, design, develop, and disseminate but this stage is only up to the develop stage. Data analysis used qualitative descriptive. The developed practice lab book is made with an interesting cover. The parts of the practicum guide book consisted of student identity, title, theoretical base, objectives, research questions, tools, materials, work steps, argumentation scheme, argumentation sessions and reports. Expert and practitioner validation results showed that the valid category is